The Price of a Smile: Hedging and Spanning in Option Markets - Buraschi, Andrea; Jackwerth, Jens (Review of Financial Studies, 2001)
The volatility smile changed drastically around the crash of 1987, and newoption pricing models have been proposed to accommodate that change. Deterministic volatility models allowfor more flexible volatility surfaces but refrain from introducing additional risk factors. Thus, options are still redundant securities. Alternatively, stochastic models introduce additional risk factors, and options are then needed for spanning of the pricing kernel. We develop a statistical test based on this difference in spanning. Using daily S&P 500 index options data from 1986–1995, our tests suggest that both in- and out-of-the-money options are needed for spanning. The findings are inconsistent with deterministic volatility models but are consistent with stochastic models that incorporate additional priced risk factors, such as stochastic volatility, interest rates, or jumps.